COMPARISON OF EFFECT OF LOCALLY AVAILABLE BRANDS OF CLOPIDOGREL ON PLATELET AGGREGATION IN PATIENTS WITH CORONARY ARTERY DISEASE - Khan, Sher Bahadar; ullah, Hameed; Noor, Lubna; Hafeezullah, Muhammad; Awan, Zahid Aslam; Din, Shahab ud (Journal of Ayub Medical College Abbottabad, 2010)
Background: Anticoagulant effect of clopidogrel is of utmost importance in coronary artery disease, especially in prevention of coronary stent thrombosis. Recently, many new local brands of clopidogrel have been launched, with unknown efficacy. This study was conducted with the aim to compare two locally prepared clopidogrel brands, in terms of the effect of a loading dose of 600 mg on inhibition of platelet aggregation in patients with coronary artery disease. Methods: This was a double blind randomised study. Sample population consisting of 35 patients, were admitted at Lady Reading Hospital, Peshawar, for the management of coronary artery disease. Baseline platelet aggregation of all these patients was measured. These patients were divided in two groups randomly. Group-A consisting of 18 patients was given brand ’˜A’ clopidogrel 600 mg, while Group-B consisting of 17 patients was give brand ’˜B’ of clopidogrel 600 mg. The platelet aggregation of both groups was then measured at baseline, and at 2, 4, and 6 hours after taking the loading dose of 600 mg. Results: Platelet aggregation time at baseline in Group-A was 2.61±2.28 sec. and in Group-B it was 2.24±1.52 sec. (p=0.57). After 2 hours of clopidogrel administration in Group-A the platelet aggregation time was 1.44±1.58 sec. and in Group-B it was 1.53±1.107 sec. (p=0.85). Platelet aggregation time after 4 hours in Group-A was 0.28±0.57 sec. and in Group-B 1.06±1.03 sec. (p=0.009), and after 6 hours it was 0.00±0.00 sec. in Group-A and in Group-B it was 0.59±0.71 sec. (p=0.001). Conclusion: The two brands of clopidogrel had a significant difference in their effect on inhibition of platelet aggregation. Different brands of clopidogrel may not be equally effective. Keywords: Platelet Aggregation, Clopidogrel, Coronary Artery Disease